Strategic city projects, legal systems and professional effectiveness - Menno Van der Veen; Willem Korthals Altes (European Regional Science Association (ERSA), 2005)
Differences between the legal systems of common law and civil law have attained attendance in the economic literature of "the new comparative economics” (Djankov et al, 2003) A relevant difference between these legal systems is in the principle of good faith, which has a specific meaning in private law. It does not only refer to a principle of honesty and fair dealing (subjective good faith) but the good faith provisions in the civil code are also a basis for a judge to interpret, supplement or even set aside contract provisions parties have agreed on (objective good faith). Whereas the principle of good faith is accepted in civil law (the law of the European continent), the common law (Anglo-American law) has until now not accepted a general (objective) good faith principle. This paper will relate this aspect of difference of these legal systems to two different models of professional practice that are developed by Argyris and Schön (1974) in the classical work "Theory in practice: increasing professional effectiveness”. The paper shows that common law system fits better with a model 1 of professional behavior and the civil law system with model 2. Relevant is that according to Argyris and Schön these models are not equally effective, i.e., "double-loop learning” would not occur in model 1, unless through revolutionary change. The paper investigates whether these theoretical insights come to the ground in strategic city projects. Two case studies are analyzed, i.e. the Mahler 4 project in the South Axis of Amsterdam and to plot 16/17 in Battery Park City, New York. It shows that the relationships between agents in these projects reflect the differences in legal systems, and that this has also consequences for professional competences. The paper proposes research questions to develop further insights in the practical meaning, to strategic urban projects, of the different doctrines of good faith in common law and civil law.
Keywords: 330